From Norms to Facts: The Realization of Rights in Common and Civil Private Law - Dedek, Helge (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
Every legal system that ties judicial decision making to a body of preconceived norms has to face the tension between the normative formulation of the ideal and its approximation in social reality. In the parlance of the common law, it is, more concretely, the remedy that bridges the gap between the ideal and the real, or, rather, between norms and facts. In the common law world—particularly in the United Kingdom and the Commonwealth—a lively discourse has developed around the question of how rights relate to remedies. To the civilian legal scholar—used to thinking within a framework that strictly categorizes terms like substance and procedure, subjective right, action, and execution—the concept of remedy remains a mystery. The lack of “remedy” in the vocabulary of the civil law is more than just a matter of attaching different labels to functional equivalents, it is the expression of a different way of thinking about law. Only if a legal system is capable of satisfactorily transposing the abstract discourse of the law into social reality does the legal machinery fulfill its purpose: due to the pivotal importance of this translational process, the way it is cast in legal concepts thus allows for an insight into the deep structure of a legal culture, and, convergence notwithstanding, the remaining epistemological differences between the legal traditions of the West. A mixed jurisdiction must reflect upon these differences in order to understand its own condition and to define its future course.